2018
DOI: 10.1007/s10535-017-0761-4
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress affects growth, content of chlorophyll, abscisic acid, Na<sup>+</sup>, and K<sup>+</sup>, and expression of novel NAC genes in contrasting rice cultivars

Abstract: Osmotic stress causes a series of morphological, physiological, biochemical, and molecular changes that alters plant growth, development, and productivity around the globe. Phytohormones, nutrients, and transcription factors may induce adaptive responses to osmotic stress in plants. We evaluated the effect of osmotic stress induced by 18.5 % polyethylene glycol (PEG) or 100 mM NaCl on growth, content of abscisic acid (ABA), chlorophyll (Chl), sodium, and potassium, and the expression of multifunctional NAC tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…However, any clearer trait difference for the model plants between brine and NaCl treatments indicates that osmotic stress is the main stress factor affecting the studied plants' growth and development. This is in line with the findings of García-Morales et al [83], Kumari et al [84], Osakabe et al [85] and Debez et al [86], who found that NaCl acts mainly by an osmotic effect. However, more detailed physiological studies are needed to compare the ionic composition of brine and single NaCl effects.…”
Section: Discussionsupporting
confidence: 92%
“…However, any clearer trait difference for the model plants between brine and NaCl treatments indicates that osmotic stress is the main stress factor affecting the studied plants' growth and development. This is in line with the findings of García-Morales et al [83], Kumari et al [84], Osakabe et al [85] and Debez et al [86], who found that NaCl acts mainly by an osmotic effect. However, more detailed physiological studies are needed to compare the ionic composition of brine and single NaCl effects.…”
Section: Discussionsupporting
confidence: 92%
“…During acclimation to drought stress, land plants follow numerous changes in their morphology like reduction of vegetative growth to limit water lose from their body. Osmotic stresses induce morphological growth-arrest along with the reduction of Chl contents in angiosperms, including rice and Arabidopsis ( Ozfidan et al, 2013 ; Kumari et al, 2014 ; García-Morales et al, 2018 ). Exposure of M. polymorpha thallus to the osmotic stressors for 15 days resulted in severe growth inhibition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, photosynthetic pigments harvest the light for photosynthesis process ( Rahneshan et al., 2018 ; Lan et al., 2020 ). Osmotic condition can injury the chlorophyll content and prevent synthesis of chlorophyll pigments, therefore chlorophyll degradation is one of the subsequences of osmotic stress ( Akbari et al., 2018 ; García-Morales et al, 2018 ). In this study, decline in chlorophyll content were observed under osmotic stress.…”
Section: Discussionmentioning
confidence: 99%